An intellectual history of political corruption - Buchan, Bruce; Hill, Lisa.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Few concepts have witnessed a more dramatic resurgence of interest in recent years than corruption. This book provides a compelling historical and conceptual analysis of corruption which demonstrates a persistent oscillation between restrictive'public office' and expansive'degenerative' connotations of corruption from classical Antiquity to 1800.
Keywords: Political science; Political theory; Public policy